Building Religious Values in Students: The Role of Extracurricular Programs at Islamic Middle School - Fathurrahman, Fathurrahman; Wahyudi, Winarto Eka; Mahfud, Sahal (Indonesian Journal of Islamic Education Studies (IJIES), 2024)
This research explores the extracurricular learning program at Tanfirul Ghoyyi Lamongan Islamic Middle School, aimed at strengthening students' religious character. The goal is to prepare a future generation that is creative, resilient, and independent. The study focuses on the steps taken by the school, the role of the principal and staff in internalizing religious values, and the supporting factors and obstacles encountered. This research uses a qualitative approach with a case study design. Data was gathered through interviews, observations, and document analysis. The data was then analyzed using condensation, exposure, and conclusion techniques. The findings reveal several key steps the school takes to strengthen students' religious character. These include formulating the goals of extracurricular activities in line with the school's vision and mission, determining the implementation team, developing curriculum programs, creating extracurricular activities, innovating learning outside the classroom, and implementing habituation, modeling, and supervision. The principal plays a crucial role in planning, organizing, and supervising the program. At the same time, supervisory teachers are responsible for enhancing religious understanding, guiding the internalization process, and training students. Support for the program comes from various sources, including the school, student guardians, the Islamic boarding school environment, the creativity of supervisory teachers, and high student interest. However, challenges include a lack of awareness among community members and parents. In conclusion, the study underscores the importance of a collaborative effort involving school administration, teachers, students, and parents in effectively strengthening students' religious character through extracurricular activities. This research provides valuable insights into the practical steps and collective efforts required to nurture a morally grounded and independent future generation.